The Development of E-UKBM Schmeckt Lecker for Class XI Students of SMA Negeri 8 Malang - Savira Chairani Vidinda (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2020)
This development research aims to develop a product in the form of E-UKBM for learning German with the theme Essen und Trinken from the sub-theme of Alltagsleben. This material is studied by high school class XI students in the even semester. This research and development model uses the ADDIE model (analysis, design, development, implementation, and evaluation) by Dick and Carey. Based on the results of validation by material experts and media experts, this E-UKBM product is suitable for use.